Banking Risk Management Strategies In Addressing Credit Issues In Indonesia - Ismail, Zakiya Az Zikra; Nathania, Nanda Riesta; Baidhowi (Abadi Institute, 2025)
The issue of credit, particularly the increasing rate of Non-Performing Loans (NPLs), has become one of the primary challenges in Indonesia’s banking sector. To address this risk, banks apply various risk management strategies to maintain financial stability and prevent more severe losses. This study aims to analyze the risk management strategies implemented by banks in tackling credit problems in Indonesia. Through effective risk management, banks can reduce NPL levels, maintain financial stability, and enhance public trust in the Indonesian banking system. This research was conducted using a qualitative method through literature analysis and secondary data obtained from various credible sources. The primary focus of this study is to examine the steps taken by banks to identify, assess, and control credit risks in order to suppress the growth of Non-Performing Loans (NPLs). Strategies implemented include the application of strict credit assessment systems, diversification of loan portfolios, and the utilization of technology to continuously monitor debtor performance. In addition, credit restructuring policies and the strengthening of corporate governance are also considered effective preventive measures to ensure financial stability.